Improvement of extraction efficiency for spectrophotometric determination of NO3- and NO2- in Gunshot residues; An application for a shooting distance study - Pluangklang, Thanakorn; Rimmai, Areerut; Sermsaeng, Kanchana; Noibungkha, Sirinapa; Lao-ngam, Charoensak; Chonsalasin, Laddawan (Naresuan University Journal: Science and Technology (NUJST); Vol 26 No 3 (2018): July-September 2018DO - 10.14456/nujst.2018.5, 2018)
This research studied parameters affecting the extraction efficiency of NO 3 - and NO 2 - from gunshot residue samples (GSRs). The spectrophotometric determination of NO 3 - and NO 2 - was carried out using the principle of a Griess reaction. For this work, both sampling and extraction parameters were investigated before selecting the optimal condition for a study of shooting distance. The results showed that a mixed solution of 1% Sulfanilamide and 1% N-(1-Naphthyl) ethylene diamine (NED) in 0.5 molL -1 HCl (Griess reagent) and 30 min reaction time provided good sensitivity for the determination of NO 2 - at 540 nm. In the case of NO 3 - , 1% VCl 3 in Griess reagent was used to reduce NO 3 - to NO 2 - before analysis with the same principle. The optimal condition for a sampling procedure used 150 µL of room temperature deionized water per cotton brush swab for two replicated GSR collections. Samples were stored for 1 week before analysis could be carried out at 4 O C in a refrigerator or at room temperature without significantly different results. On the other hand, 4 mL of room temperature deionized water with and without ultrasonic extraction times of 5 or 30 min respectively were the selected parameters for NO 2 - and NO 3 - extraction from GSRs.      The proposed method could be applied completely for spectrophotometric determination of NO 3 - and NO 2 - in GSRs. The limits of detection (LOD) of NO 2 - and NO 2 - + NO 3 - were 0.27×10 -6 and 3.58×10 -6 molL -1 respectively with a relative standard deviation of the given slope. A wide linearity range between 2.17×10 -6 to 217×10 -6 molL -1 was obtained and a percentage of recovery in the range of 96.24 – 102.32 and 98.04 – 105.96 for NO 3 - and NO 2 - was achieved, respectively. This method can be performed for determination of NO 3 - and NO 2 - content at a maximum 304.8 centimeter shooting distance. From these findings, the proposed sampling, extracting and determining methods for NO 3 - and NO 2 - in GSRs are highly sensitive, precise, robust, simple and inexpensive, with a short analysis time and provide a useful alternative procedure for analytical chemists or forensic scientists in their work. Keywords: Extraction, NO 3 - and NO 2 - , Gunshot residues